Towards Fluorescence In Vivo Hybridization (FIVH) Detection of H. pylori in Gastric Mucosa Using Advanced LNA Probes - Sílvia Fontenete (2015)
In recent years, there have been several attempts to improve the diagnosis of infection caused by Helicobacter pylori. Fluorescence in situ hybridization (FISH) is a commonly used technique to detect H. pylori infection but it requires biopsies from the stomach. Thus, the development of an in vivo FISH-based method (FIVH) that directly detects and allows the visualization of the bacterium within the human body would significantly reduce the time of analysis, allowing the diagnosis to be performed during endoscopy. In a previous study we designed and synthesized a phosphorothioate locked nucleic acid (LNA)/2' O-methyl RNA (2'OMe) probe using standard phosphoramidite chemistry and FISH hybridization was then successfully performed both on adhered and suspended bacteria at 37 degrees C. In this work we simplified, shortened and adapted FISH to work at gastric pH values, meaning that the hybridization step now takes only 30 minutes and, in addition to the buffer, uses only urea and probe at non-toxic concentrations. Importantly, the sensitivity and specificity of the FISH method was maintained in the range of conditions tested, even at low stringency conditions (e.g., low pH). In conclusion, this methodology is a promising approach that might be used in vivo in the future in combination with a confocal laser endomicroscope for H. pylori visualization.